Changes in serum albumin concentrations during transition to dialysis and subsequent risk of peritonitis after peritoneal dialysis initiation: a retrospective cohort study - Kajohnsak Noppakun (2020)
© 2020, Italian Society of Nephrology. Background: Evidence shows that lower serum albumin concentrations are associated with the risk of peritoneal dialysis (PD)-related peritonitis. However, little is known regarding its relationship and magnitude of change before PD initiation and peritonitis risk. Methods: We performed a multicenter retrospective cohort study on 1169 adult cases of PD in Thailand. The associations of serum albumin at concentration (< 2.5, 2.5–3.5, > 3.5 [reference] g/dL) and changes (unchanged + 0.1 to − 0.1 [reference], decrease or increase > 0.1 g/dL) over 3- and 6-month before PD initiation with PD-related peritonitis were examined. Time-to-first and longitudinal rates of peritonitis were examined using the multivariable Cox proportional hazards model and Poisson regression analyses, respectively. Results: At baseline PD initiation, patients with serum albumin concentration < 2.5 and 2.5–3.5 g/dL had an adjusted hazard ratio (HR) of 1.69 and 2.0 times higher peritonitis (vs. > 3.5 g/dL), respectively. Compared to the unchanged group, patients with a decrease and increase in serum albumin concentrations during transitioning to dialysis were significantly associated with higher and lower risk of peritonitis, adjusted HR of 2.25 (95% confidence interval [CI] 1.85–2.75) and 0.53 (95% CI 0.42–0.68) over three-month, and 1.43 (95% CI 1.15–1.79) and 0.64 (95% CI 0.52–0.79) over six-month, respectively. Similar trends of longitudinal rates of serum albumin concentrations and peritonitis risk were observed. Conclusions: Serum albumin concentrations at PD initiation and its magnitude of change during the transition to dialysis are strongly associated with subsequent risk of peritonitis. Further studies are required on strategies modifying serum albumin concentration during the transition to PD.